Controlling the morphology and composition of Ag/AgBr hybrid nanostructures and enhancing their visible light induced photocatalytic properties. Issue 60 (7th June 2016) - Shahzad, Aasim; Yu, Taekyung; Kim, Woo-Sik
Abstract : Ag/AgBr hybrid nanostructures were prepared by reducing AgBr nanoparticles synthesized by reaction of Ag + with Br − . The Ag/AgBr hybrid nanostructures exhibited enhanced photocatalytic activity and recyclability for decomposing methylene blue (MB). Abstract : Here, we report a simple and fast synthetic route to Ag/AgBr hybrid nanostructures prepared by reducing AgBr nanoparticles synthesized by the reaction of Ag + with Br − in the presence of polyethyleneimine (PEI). By controlling the experimental conditions including reaction temperature and amount of reducing agent, we could easily control the morphology and composition of a variety of Ag/AgBr hybrid nanostructures including Ag nanoparticles decorated with AgBr nanoparticles and hollow cage-like Ag-rich nanostructures. The Ag/AgBr hybrid nanostructures exhibited enhanced photocatalytic activity and recyclability for decomposing methylene blue (MB) under visible-light illumination because of a small bandgap (2.6 eV) and strong SPR effect. In particular, we found that the Ag/AgBr hybrid nanostructures showed a photocatalytic reaction rate that was 1000 times faster than commercial TiO2 (P-25). In addition, the Ag/AgBr hybrid nanostructures had a higher photocatalytic activity compared to Ag/AgCl hybrid nanostructures towards the decomposition of methyl orange (MO) under visible light illumination.